Pendampingan Pemanfaatan Limbah Buah Jeruk Sebagai Pupuk Organik Cair di Desa Sumber Bakti Kecamatan Darul Makmur Kabupaten Nagan Raya - Afrillah, Muhammad; Rahmat Pramulya; Banta Diman; Sumeinika Fitria Lizmah (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2024)
Sumber Bakti Hamlet, Makarti Jaya Village is one of the orange-producing villages that supports economic activities in the area. However, the orange farmer group faces several problems, such as (Product Diversification), Farmers do not utilize garden waste (damaged oranges) and sorting waste (undergrade oranges), (Knowledge): Farmers do not understand the process of producing organic fertilizer as a valuable product in providing direct contributions. The purpose of this community service activity is to increase public understanding of the benefits of liquid organic fertilizer; improve the ability of the Tunas Muda Sumber Bakti Farmer Group through the application of product design management for processing orange waste into liquid organic fertilizer; and increase the productivity of the Tunas Muda Sumber Bakti Farmer Group through processing orange waste into liquid organic fertilizer. Based on the results of the evaluation of all participants who took part in the activity, it showed that after the training activity was carried out, there was an increase in understanding and skills in all training participants. Tunas Muda Sumber Bakti Farmer Group Knows the proper and correct management of organic waste before training 23%, and after training 100%, Understands organic fertilizer in general before training 61.5%, and after training 92.8%, Knows the utilization and processing of citrus waste before training 7.6%, and after training 92.3%, Able to make citrus waste liquid organic fertilizer before training 0%, and after training 92.3%.